Do all the patients with gastric parietal cell antibodies have pernicious anemia?. (7th September 2012) - Sun, A; Wang, YP; Lin, HP; Chia, JS; Chiang, CP
<x xml:space="preserve">Abstract</x> Objective This study evaluated whether all the patients with serum gastric parietal cell antibody (GPCA) positivity had pernicious anemia (PA). Materials and Methods The blood hemoglobin (Hb), iron, and vitamin B12 concentrations, and mean corpuscular volume (MCV) in 124 GPCA‐positive patients were measured and compared with the corresponding data in 124 age‐ and sex‐matched healthy controls. PA was defined by World Health Organization (WHO) as having an Hb concentration < 13 g dl−1 for men and < 12 g dl−1 for women, an MCV ≥ 100 fl, and a serum vitamin B12 level < 200 pg ml−1. Results We found that 20, 25, and 20 GPCA‐positive patients had deficiencies of Hb (men < 13 g dl−1, women < 12 g dl−1), iron (<60 μg dl−1), and vitamin B12 (<200 pg ml−1), respectively. Moreover, 16 GPCA‐positive patients had abnormally high MCV (≥100 fl). GPCA‐positive patients had a significantly higher frequency of Hb, iron, or vitamin B12 deficiency and of abnormally high MCV (all P‐values < 0.001) than healthy controls. However, only 12.9% of 124 GPCA‐positive patients were diagnosed as having PA by the WHO definition. Conclusion Only 12.9% of GPCA‐positive patients are discovered to have PA by the WHO definition.